THE EFFECT OF MAZE GAMES ON STORY TELLING ABILITY CHILDREN AGED 5-6 YEARS AT NURUL FADHILAH KINDERGARTEN KAB. GOWA - Nurdini, Amirah; ., rusmayadi; asti, sri wahyuni (Jurnal Jendela Bunda Program Studi PG-PAUD Universitas Muhammadiyah Cirebon, 2023)
The purpose of this study was to determine the effect of Maze game on the storytelling ability of children aged 5-6 years at Nurul Fadhilah Kindergarten, Gowa Regency. This research uses quantitative methods using quasi experimental design methods. This study targets the population of group B children aged 5-6 years at Nurul Fadhilah Kindergarten, Gowa Regency. This study used purposive sampling as a sampling method. The sample of this study amounted to 24 children where 12 children from group B3 as the experimental group and 12 children from group B1 as the control group. The results showed that the storytelling ability of children who received Maze game treatment in the experimental class was superior compared to the control class. Data analysis showed that the average score of the experimental group was 19.42, compared to 17.42 in the control group. The test result shows (2-tailed) 0.000 <0.05, then Ho is rejected and Ha is accepted. Thus, it can be concluded that children aged 5 to 6 years at Nurul Fadhilah Kindergarten, Gowa Regency showed a significant increase in storytelling ability after playing the Maze game.